Association between thermogenic brown fat and genes under positive natural selection in circumpolar populations - Yuka Ishida; Mami Matsushita; Takeshi Yoneshiro; Masayuki Saito; Kazuhiro Nakayama (Journal of Physiological Anthropology, 2024)
Abstract Background Adaptation to cold was essential for human migration across Eurasia. Non-shivering thermogenesis through brown adipose tissue (BAT) participates in cold adaptation because some genes involved in the differentiation and function of BAT exhibit signatures of positive natural selection in populations at high latitudes. Whether these genes are associated with the inter-individual variability in BAT thermogenesis remains unclear. In this study, we evaluated the potential associations between BAT activity and single nucleotide polymorphisms (SNPs) in candidate gene regions in East Asian populations. Methods BAT activity induced by mild cold exposure was measured in 399 healthy Japanese men and women using fluorodeoxyglucose-positron emission tomography and computed tomography (FDG-PET/CT). The capacity for cold-induced thermogenesis and fat oxidation was measured in 56 men. Association analyses with physiological traits were performed for 11 SNPs at six loci (LEPR, ANGPTL8, PLA2G2A, PLIN1, TBX15-WARS2, and FADS1) reported to be under positive natural selection. Associations found in the FDG-PET/CT population were further validated in 84 healthy East Asian men and women, in whom BAT activity was measured using infrared thermography. Associations between the SNP genotypes and BAT activity or other related traits were tested using multiple logistic and linear regression models. Results Of the 11 putative adaptive alleles of the six genes, two intronic SNPs in LEPR (rs1022981 and rs12405556) tended to be associated with higher BAT activity. However, these did not survive multiple test comparisons. Associations with lower body fat percentage, plasma triglyceride, insulin, and HOMA-IR levels were observed in the FDG-PET/CT population (P < 0.05). Other loci, including TBX15-WARS2, which is speculated to mediate cold adaptation in Greenland Inuits, did not show significant differences in BAT thermogenesis. Conclusions Our results suggest a marginal but significant association between LEPR SNPs. However, ...